A cluster of sulfatase genes on Xp22.3: mutations in chondrodysplasia punctata (CDPX) and implications for warfarin embryopathy - Franco, Brunella; Meroni, Germana; Parenti, Giancarlo; Levilliers, Jacqueline; Bernard, Loris; Gebbia, Marinella; Cox, Liza; Maroteaux, Pierre; Sheffield, Leslie; Rappold, Gudrun; Andria, Generoso; Petit, Christine; et al. (Cell, 1995)
X-linked recessive chondrodysplasia punctata (CDPX) is a congenital defect of bone and cartilage development characterized by aberrant bone mineralization, severe underdevelopment of nasal cartilage, and distal phalangeal hypoplasia. A virtually identical phenotype is observed in the warfarin embryopathy, which is due to the teratogenic effects of coumarin derivatives during pregnancy. We have cloned the genomic region within Xp22.3 where the CDPX gene has been assigned and isolated three adjacent genes showing highly significant homology to the sulfatase gene family. Point mutations in one of these genes were identified in five patients with CDPX. Expression of this gene in COS cells resulted in a heat-labile arylsulfatase activity that is inhibited by warfarin. A deficiency of a heat-labile arylsulfatase activity was demonstrated in patients with deletions spanning the CDPX region. These data indicate that CDPX is caused by an inherited deficiency of a novel sulfatase and suggest that warfarin embryopathy might involve drug-induced inhibition of the same enzyme.
Gesehen am 30.03.2021